5′-UTR allelic variants and expression of the lycopene-ɛ-cyclase LCYE gene in maize (Zea mays L.) inbred lines of Russian selection - D. Kh. Arkhestova; B. R. Shomakhov; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции)
In breeding, biofortification is aimed at enriching the edible parts of the plant with micronutrients. Within the framework of this strategy, molecular screening of collections of various crops makes it possible to determine allelic variants of genes, new alleles, and the linkage of allelic variants with morphophysiological traits. The maize (Zea mays L.) is an important cereal and silage crop, as well as a source of the main precursor of vitamin A – β-carotene, a derivative of the β,β-branch of the carotenoid biosynthesis pathway. The parallel β,ε-branch is triggered by lycopene-ε-cyclase LCYE, a low expression of which leads to an increase in provitamin A content and is associated with the variability    of the 5’-UTR gene regulatory sequence. In this study, we screened a collection of 165 maize inbred lines of Russian selection for 5’-UTR LCYE allelic variants, as well as searched for the dependence of LCYE expression levels on the 5’-UTR allelic variant in the leaves of 14 collection lines. 165 lines analyzed were divided into three groups carrying alleles A2 (64 lines), A5 (31) and A6 (70), respectively. Compared to A2, allele A5 contained two deletions (at positions -267–260 and -296–290 from the ATG codon) and a G251→T substitution, while allele A6 contained one deletion (-290–296) and two SNPs (G251→T, G265→T). Analysis of LCYE expression in the leaf tissue of seedlings from accessions of 14 lines differing in allelic variants showed no associations of the 5’-UTR LCYE allele type with the level of gene expression. Four lines carrying alleles A2 (6178-1, 6709-2, 2289-3) and A5 (5677) had a significantly higher level of LCYE gene expression (~0.018–0.037) than the other 10 analyzed lines (~0.0001–0.004), among which all three allelic variants were present.